BRIGIF SYNERGITY ANALYSIS OF 4 MARINES/BS AND LAMPUNG SEA CULTURAL FISHERIES CENTER FOR MARITIME POTENTIAL DEVELOPMENT - P, I Wayan Agus; Nugroho, Hervianto; Widodo, Sunarjo Slamet (Asian Journal of Aquatic Sciences, 2022)
In the framework of the maritime potential development program, Dankormar issued a telegram Number ST/701/2020 dated April 9, 2020 regarding the Implementation of the Food Security Program through concrete steps. Brigif 4 Marines/BS is the implementing command unit for Kormar in Lampung. In its implementation, Brigif 4 Marines/BS needs to carry out communication and creativity for the Binpotmar program in synergy with the Lampung Marine Aquaculture Center. By using SPSS version 25 method, it is known that the effect of communication and creativity is partially 16.2% and 28.3%. Then the effect of synergy or simultaneously between Brigif 4 Marines / BS and the Lampung Marine Cultivation Fisheries Center is 35.3%. According to the Guilford criteria, the correlation is quite significant, which is 0.594. So that there needs to be a more intensive and more well-established improvement between the Brigif 4 Marines/BS and the Lampung Marine Aquaculture Center, which is expected to improve the welfare of the people of Lampung.